Pathogenic bacterial contamination of carcasses from outdoor organically reared pigs: preliminary results from a survey in Northern Italy - Rampin F.; Schiavon E.; Luciano I.; Sartori A.; Bondesan V. (7th International Symposium on the Mediterranean Pig, 2012)
Organic pigs often are reared and fattened outdoor; this production system normally affects skin cleanliness especially during wet season. The slaughtering of very dirty pigs may increase the risk of carcass contamination. The following survey investigates the presence of several pathogenic bacterial for human foodborne such as Listeria monocitogenes, Salmonella spp., Escherichia coli O157, Yersinia enterocolitica and Campylobacter spp. Different samples (skin swab sponges performed before and after slaughtering, faeces, tonsils and rind) from risky areas for contamination have been collected from 31 fattened pigs coming from 7 organic farms and slaughtered in 3 small abattoirs. None of those samples were positive for Salmonella spp. Campylobacter spp., was found on 64.5 % of samples (77% of samples were positive for Campylobacter coli). Listeria monocytogenes and Yersinia enterocolitica were detected on 13% and 6.5% of samples respectively; Escherichia coli O157 was found only on 3.2% of considered samples. Preliminary results on the level of carcass contamination show similar figures as found in literature for Campylobacter spp., Listeria monocitogenes and Yersinia enterocolitica, both for the outdoor organic pigs and the conventional ones. The high presence of Campylobacter spp. in faeces suggests to pay particular attention during evisceration to prevent carcass contamination.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)